Women’s Autonomy And Utilization of Maternal Health Services In Rural Tertiary Level Hospital of Karnali Province, Nepal - Ojha, Sujata; Lama, Monika; Shrestha, Sharmila; Maharjan, Ramu; Bhattarai, Sarswoti Gautam; Awasthi, Mona (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aim: To assess the effect of women’s autonomy on utilization of maternal health services in selected tertiary level hospital of Karnali Province. Methods: Cross sectional descriptive research design was adopted in Karnali Academy of Health Science (KAHS). Nepal. Pregnant women after 22 weeks of gestation to term who came for the delivery in KAHS irrespective of mode of delivery and postnatal women within 6 weeks postpartum irrespective of place and mode of delivery were taken as study population. Probability sampling technique was used. Semi-structured interview schedule was used to collect data after informed consent. Result: The study found that 52.5 percent of respondents utilized maternal health services and 38.6 percent had full autonomy in their life in regards to movement, financial and decision making autonomy. Significant association was found between utilization of maternal services and women autonomy. Regarding the effect of autonomy on maternal health service utilization, significant association was seen between movement autonomy and utilization of maternal health services (p-value= .002, OR= 0.432, C.I: 0.253-0.735). Income, facilities of transportation and decision making power of husband are the factors affecting utilization of maternal health services. Conclusions: The study provides more insight between the utilization of maternal health services and autonomy of women, lower the movement autonomy of the women lower the utilization of maternal health services. Actions that increase women’s autonomy at home could be effective in helping assure good maternal health. Keywords: maternal health services, women’s autonomy, utilization